Utilization Of Wet And Dry Waste Into Products That Have Economic Value To Support The Residents Of The Village Of Bandar Khalifah, Percut Sei Tuan District As Additional Income - Errie Margery; Wan Suryani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Bandar Khalipah village is one of the villages located in Percut Sei Tuan District, Deli Serdang Regency North Sumatra Province with an area of 883 hectares. Administratively Bandar Khalipah village consists of seventeen hamlets.Currently the role of the village apparatus in carrying out its function of protecting the community is quite good and acts as a motivator and the mediator in the community is quite good and plays an active role as amotivator and mediator in the community the cooperation of the village apparatus and its apparatus(hamlet head) is going well. It is known thay on average local residents are also the majority of their income from labor and farming. Those who have uncertain incomes and also have problems faced by the residents of Bandar khalipah village are household waste that is not managed properly, therefore by managing household waste both wet and dry to be used as products of economic value, namely eco enzymes and briquettes can help the economy of the village of Percut Sei Tuan sub-district as additional income and the surrounding environment becomes cleaner.